Fostering Mobile Payment Adoption: A Case of Near Field Communication (NFC) - Fauzan Aris; Kamisah Ismail; Suhana Mohezar (International Journal of Business and Society, 2022)
This study aims to investigate the adoption intention of NFC mobile payment services among consumers in Malaysia. Data collected from 218 respondents were analysed using Partial-Least-Square. The results reveal that consumers’ technology readiness is positively related with perceived usefulness, perceived ease of use and intention to adopt NFC. Technology availability has also provided similar results regarding its relationship with perceived ease of use and intention to adopt NFC. The results also show the mediation effects of perceived ease of use and perceived usefulness of the technology in the relationship between technology availability and perceived usefulness, as well as between perceived ease of use and intention to adopt NFC, respectively. The findings of this study suggest the need for the industrial player to target the group of consumers who are innovative. It is also important for banking institutions to reinvent the card system to support NFC infrastructure, so that mass adoption could be created. This study fills the research voids by integrating the established mobile technology acceptance model with two constructs – consumers’ technology readiness and technology availability.